FORMATIVE ASSESSMENT IN MATHEMATICS SCIENCES - de Souza Holanda, Magno (Journal of Interdisciplinary Debates, 2024)
The Learning Assessment Process in the science of mathematics is the topic of this discussion, it has its starting point in the universe of Education, whose delimitation takes place within the scope of Brazil, in which it perceives the expressions of the assessment of school Learning. Asking how you identify this process. The objective is to understand the opportunities brought by this theme to reflect on the subject. And, to achieve this, it is necessary to present concepts of Learning Assessment and pedagogical practice, understand their contributions to teaching and show the aspects of this application. The methodology is bibliographic, the search was for the terms “Process” “Evaluation” in “mathematics”, collecting samples from the universe informed in the Scielo and Google Scholar search bars. At the end, we review the text, realizing some points considered highly relevant to elucidating the problem, realizing that the assessment of school learning has been the subject of constant discussions within the educational scenario, presenting itself as an inexhaustible source of questions that are raised within the school community.